Religiositas Sebagai Variabel Mediasi Antara Islamic Work Ethic Terhadap Organizational Citizenship Behavior Pada Guru MTs - Salma Fatimah Azzahroh; Maharani Tyas Budi Hapsari (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
In increasingly complex work environments, teachers’ work behavior in madrasahs is not solely driven by formal job responsibilities but also by intrinsic awareness to contribute beyond assigned duties. However, reliance on external motivation, such as additional incentives, may limit the emergence of voluntary and proactive behaviors when not accompanied by material rewards. This study aimed to examine the effect of Islamic Work Ethic (IWE) on Organizational Citizenship Behavior (OCB), with religiosity as a mediating variable among madrasah teachers. A quantitative research approach was employed involving 108 respondents selected using purposive sampling. The research instruments were adapted from previous studies and demonstrated strong psychometric properties, with validity coefficients ranging from 0.92 to 1.00 and reliability coefficients of 0.975 for IWE, 0.970 for OCB, and 0.970 for religiosity. Data analysis was conducted using PROCESS Macro for SPSS version 4.2 to test the mediation effect. The results indicated that Islamic Work Ethic had a positive and significant effect on Organizational Citizenship Behavior. Furthermore, religiosity was found to significantly mediate the relationship between IWE and OCB. Teachers with higher levels of religiosity tend to internalize Islamic work values more deeply, which in turn fosters responsible, cooperative, and committed behaviors within the madrasah environment. These findings highlight the importance of integrating spiritual and ethical values into organizational practices. The study provides practical implications for Islamic educational institutions, particularly madrasahs, in strengthening Islamic Work Ethic and religiosity among teachers through structured spiritual development programs and the integration of Islamic values into organizational culture.